Study of Biological Features of Frozen-Thawed Saccharomyces cerevisiae Yeast Cells Incapsulated in Alginate Granules - Ponomareva, Viktoriya L.; Vysekantsev, Igor P.; Onasenko, Elena S. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):179.